Synchronization of phase and frequency in flyback inverter using a new ripple hysteresis controller - Gongzhuo, Chen; Radin Za'im,; Yushaizad Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this paper, a novel approach called ripple hysteresis controller (RHC) is proposed. Previously current signal and hysteresis band are controlled independently in the hysteresis conventional controller (HCC). However, the HCC are unable to achieve a stable current frequency due to the current signal inside the hysteresis band is less immune to disturbance and fluctuates when external signals interfere with it. To solve the problem of HCC inability to effectively control the frequency and phase of the current signal, the RHC is introduced. It is based on a novel double closed-loop control model. Firstly, a closed-loop control is carried out to compare and evaluate the frequency variation and phase synchronization of the magnetizing current. Secondly, the closed-loop control is utilised to control the hysteresis controller band. The new RHC approach is demonstrated using the MATLAB Simulink tool to substantially reduce the output ripple error of current and voltage as well as to enhance the transition accuracy at zero crossing in comparison to the HCC. This study focuses on the mathematical foundations of RHC, simulation design and result analysis. The results of the simulation illustrate the effectiveness of this innovative RHC in overcoming varying frequency and phase. In conclusion, this novel method has successfully validated the proposed RHC performance for flyback inverter application and demonstrated its superiority over HCC in several aspects.